Laporan Evaluasi Keuangan Perusahaan Subsektor Transportasi Udara - Stevu Denito, Steven; Hendra Kusuma, Helmy; Giovany, Kenny; Carlo, Ronald; M Safari, Jenjen; Ramadhan, Yanuar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The area generally impacted by versatility limitations because of the Coronavirus pandemic is transportation. This exploration was directed to assess organization funds for 3 transportation organizations. Descriptive, quantitative research methods are utilized in this study. The examples utilized in this exploration were 3 transportation organizations, to be specific PT. Garuda Indonesia Tbk. ( GIAA), PT. Air Asia Indonesia Tbk. ( CMPP), and PT. Jaya Trishindo Tbk. ( HELI). Information is utilized to examine the degree of information on organization monetary assessments utilizing proportion investigation, normal size examination, pattern investigation and record investigation. The findings of the study demonstrate that PT's profitability ratio and liquidity ratio value Indonesia Tbk. Garuda GIAA) and PT. Air Asia Indonesia Tbk. encountered a decrease in 2021, yet expanded in 2022. In the interim, the organization PT. Jaya Trishindo Tbk. from 2020 to 2022 the benefit proportion keeps on declining. PT movement proportion esteem. Garuda Indonesia Tbk. from 2020 to 2022 there will in general be an increment, while PT. Tbk. Air Asia Indonesia and PT. Jaya Trishindo Tbk. tends to go down in 2021, but it will go up in 2022. The influence proportion upsides of the three organizations will generally vacillate or go all over from 2020 to 2022. In light of the normal size computation, it very well may be reasoned that PT. Garuda Indonesia Tbk. and PT. Air Asia Indonesia Tbk. suffered losses in 2020 and 2021, but will gradually improve and grow in 2022. In the interim the organization PT. Trishindo Tbk, Jaya as a matter of fact created a gain in 2020 and 2021, while in 2022 it really encountered a misfortune. In view of pattern estimations it very well may be presumed that PT. Garuda Indonesia Tbk., PT. Air Asia Indonesia Tbk., and PT. Jaya Trishindo Tbk. experienced misfortunes in 2021 and 2022. In light of the file estimation it tends to be presumed that PT. Indonesia Tbk. Garuda and PT. Jaya Trishindo Tbk. it made a profit in 2020 and 2021, but it lost money in 2022. In the interim the organization PT. Air Asia Indonesia Tbk. actually made money between 2020 and 2022.